2018
DOI: 10.1001/jamaophthalmol.2018.2257
|View full text |Cite
|
Sign up to set email alerts
|

Automated Quantification of Nonperfusion Areas in 3 Vascular Plexuses With Optical Coherence Tomography Angiography in Eyes of Patients With Diabetes

Abstract: IMPORTANCE Diabetic retinopathy (DR) is a leading cause of vision loss that is managed primarily through qualitative clinical examination of the retina. Optical coherence tomography angiography (OCTA) may offer an objective and quantitative method of evaluating DR. OBJECTIVE To quantify capillary nonperfusion in 3 vascular plexuses in the macula of eyes patients with diabetes of various retinopathy severity using projection-resolved OCTA (PR-OCTA). DESIGN, SETTING, AND PARTICIPANTS Cross-sectional study at a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 23 publications
3
81
0
3
Order By: Relevance
“…Recent studies using OCTA as well as FA have quantitatively evaluated capillary nonperfusion areas in DR, and have generally demonstrated that capillary nonperfusion increases with increasing DR severity. 13,20,21 The results herein agree with these findings (Table). Furthermore, compared to FA, OCTA can also visualize periarterial capillary-free zones [16][17][18] and vessel connections at the level of precapillary arterioles and venules.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies using OCTA as well as FA have quantitatively evaluated capillary nonperfusion areas in DR, and have generally demonstrated that capillary nonperfusion increases with increasing DR severity. 13,20,21 The results herein agree with these findings (Table). Furthermore, compared to FA, OCTA can also visualize periarterial capillary-free zones [16][17][18] and vessel connections at the level of precapillary arterioles and venules.…”
Section: Discussionsupporting
confidence: 91%
“…Using OCTA to assess the retinal vascular density in diabetic eyes without clinically visible DR, researchers have drawn mixed conclusions. For example, Dimitrova et al 16 and Hwang et al 29 showed significantly reduced parafoveal VAD in both the superficial and deep retinal capillary plexuses in diabetic eyes without retinopathy compared to controls, while Simonett et al 30 and Carnevali et al 15 reported significantly reduced parafoveal VAD in the deep but not in the superficial plexus in diabetic eyes without retinopathy. In contrast, other groups demonstrated that no significant differences were found in the superficial, deep, or whole parafoveal VAD between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies also showed that additional segmentation and evaluation of the intermediate retinal layer from the superficial and deep retinal layers may enhance the ability of OCTA to detect early microvascular changes in diabetic eyes. 29,32,33 In this study, VAD and VSD were measured on the SRL, IRL, and DRL using our validated semiautomated segmentation algorithm. Our study showed that no significant difference was found in VSD or VAD in diabetic eyes without retinopathy compared to controls within the three vascular plexuses for a 6 × 6-mm scanning protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has recently developed projection-resolved OCTA (PR-OCTA) algorithm 33,34 to significantly suppress projection artifacts, allowing for proper segmentation of retinal circulation, and in turn more reliable visualization and quantification of microvasculature. [35][36][37][38][39][40][41][42][43][44][45] In this study, we aim to characterize the alterations in perfusion in all three retinal plexuses, as well as the relationship between vascular and structural changes in RP patients.…”
Section: Introductionmentioning
confidence: 99%